2012
DOI: 10.1111/j.2042-7158.2012.01487.x
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective drug–protein interaction between mexiletine and plasma protein

Abstract: hAGP may be one of the key proteins leading to the enantioselective protein bindings of mexiletine in human plasma (R>S). The residues Arg90, Leu79, Ser89 and Phe89 of hAGP may have important roles in the observed enantioselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…In particular, the (R)-enantiomer presented a downfield sense of the 1 H NMR signal non-equivalence, in agreement with what observed for the other studied mexiletine analogues [32]. Actually, recent studies showed that the binding of mexiletine enantiomers to human serum proteins was enantioselective [33,34]. Herein, we synthesized nonracemic MHM enantiomers as tools that can be used to study the enantioselectivity of this class of voltage-gated sodium channel blockers.…”
Section: Resultssupporting
confidence: 84%
“…In particular, the (R)-enantiomer presented a downfield sense of the 1 H NMR signal non-equivalence, in agreement with what observed for the other studied mexiletine analogues [32]. Actually, recent studies showed that the binding of mexiletine enantiomers to human serum proteins was enantioselective [33,34]. Herein, we synthesized nonracemic MHM enantiomers as tools that can be used to study the enantioselectivity of this class of voltage-gated sodium channel blockers.…”
Section: Resultssupporting
confidence: 84%
“…Plasma protein binding studies were conducted using an ultra filtration technique (Yu et al ., ). Briefly, freshly collected rat blank plasma samples were spiked with 20 μg·mL −1 of racemic warfarin with and without ETV (25 μg·mL −1 ).…”
Section: Methodsmentioning
confidence: 97%
“…Monti et al combined molecular mechanisms (MM) and molecular dynamics (MD) with circular dichroism (CD) to identify the main interactions between ketoprofen enantiomers and the surrounding amino acids at short distances in bovine serum albumin 51 . Similarly, Yu et al took advantage of MM and MD to identify several key residues that are involved in the enantioselectivity for the binding of AGP to mexiletine enantiomers, such as Arg90 43 .…”
Section: Methods and Modelsmentioning
confidence: 99%